Auditing of company financial standing using aggregate measure - Kowalak, Robert (Ocena kondycji finansowej przedsiębiorstwa z wykorzystaniem syntetycznego miernika, 2020)
A model of evaluation of company financial standing is presented in the article, based on the concept of aggregate synthetic measure. By calculating threshold values for the aggregate measure, statutory auditors gain a valuable tool to help determine the potential breach of company financial sustainability as well as evaluate company financial standing relative to other reporting periods. The main purpose of the author was to present a new conception of analysis company financial standing based on matrix measure. Theoretical and empirical methods are used in the paper. The theoretical part describes own model based on matrix measure. The empirical part shows the use of the model to analyze the financial condition of a stock exchange enterprise. Research methods concentrated on data and information collected from one company (case study), induction, deduction and literature analysis
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 1, s. 14-22
Keywords: financial analysis; aggregate measure; financial ratios; analiza finansowa; miernik zagregowany